2006
DOI: 10.1063/1.2385859
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of electrical properties in polycrystalline BiFeO3 thin films

Abstract: Ferroelectric BiFeO3 thin films were grown on Pt∕TiO2∕SiO2∕Si substrates by pulsed-laser deposition. From the x-ray diffraction analysis, the BiFeO3 thin films consist of perovskite single phase, and the crystal structure shows the tetragonal structure with a space group P4mm. The BiFeO3 thin films show enhanced electrical properties with low leakage current density value of ∼10−4A∕cm2 at a maximum applied voltage of 31V. This enhanced electrical resistivity allowed the authors to obtain giant ferroelectric po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
94
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(108 citation statements)
references
References 13 publications
14
94
0
Order By: Relevance
“…[1][2][3] Large remnant polarizations P r (above 60 μC/cm 2 ) have been reported for BFO films fabricated by various deposition methods. [4][5][6][7][8] Hence, BFO is expected to be a promising Pb-free ferroelectric material for realizing environment-friendly and highly-integrated ferroelectric random access memories (FeRAMs). 9,10) On the other hand, as serious problems for the industrial application of FeRAMs using BFO films, there are large leakage currents and large coercive fields E c (generally, 300-400 kV/cm) [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Large remnant polarizations P r (above 60 μC/cm 2 ) have been reported for BFO films fabricated by various deposition methods. [4][5][6][7][8] Hence, BFO is expected to be a promising Pb-free ferroelectric material for realizing environment-friendly and highly-integrated ferroelectric random access memories (FeRAMs). 9,10) On the other hand, as serious problems for the industrial application of FeRAMs using BFO films, there are large leakage currents and large coercive fields E c (generally, 300-400 kV/cm) [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] It was found that the conductivity could be reduced by optimizing the growth procedures.…”
mentioning
confidence: 99%
“…However, these films often show sizable electrical leakage currents. [11][12][13][14][15][16] These can mask measurements of the polarization loop and could short-circuit ferroelectric storage devices, so there have been extensive efforts to reduce the leakage currents. [14][15][16] It is therefore of interest to know the band gap of BiFeO 3 and its conduction mechanisms, in order to know if the leakage is intrinsic or extrinsic.…”
mentioning
confidence: 99%
“…Recently, growth technique of BiFeO 3 thin films have gathered much attention because pulsed laser deposition (PLD) provided films with excellent ferroelectric properties compared to bulk samples [4,5]. Chemical solution deposition is another attractive candidate for low-cost and efficient growth of BiFeO 3 films [6].…”
Section: Introductionmentioning
confidence: 99%